A case report of a novel mutation in lamin A/C gene related with risk of sudden death. Issue 4 (22nd March 2022) - Sanchez Vallejo, Carlos Andres; Rodriguez Ariza, Carlos Daniel; Restrepo Urbina, Jose Alfredo; Callegari Osorio, Santiago
Abstract: Background: Lamin A/C-associated heart disease is a group of clinical entities characterized by a mutation in the LMNA gene. Multiple cardiac phenotypes have been described, including a higher risk of sudden death. Case summary: A 23-year-old asymptomatic patient with an extensive history of heart disease in the family consulted the clinic. He had a genetic test performed when he was born revealing a new frameshift mutation in the LMNA gene. Numerous cardiac function tests were ordered, which initially were normal. After a year of follow-up, Holter monitoring was positive for episodes of nonsustained ventricular tachycardia (NSVT). Because of the risk factors and higher likelihood of sudden death, a decision was made to offer an implantable cardiac defibrillator (ICD), which was performed without complications. The patient continues the follow-up with cardiology and electrophysiology consisting of yearly cardiac imaging and device recordings. Discussion: Lamins are nuclear proteins involved in various cellular processes in myocardial cells. Therefore, mutations are associated with wide phenotypic alterations. The mutation described here was not previously reported in the literature. In the face of an undescribed mutation, the decision to use an ICD for primary prevention of sudden death is challenging. Because of the episodes of NSVT and a higher likelihood of risk of sudden death due to male sex and first-degree atrioventricular block, the decision to use an ICD was made for this patient, with no complications.